Adverse Selection vs Discrimination Risk with Genetic Testing. An Experimental Approach - David Bardey; Philippe De Donder; Cesar Mantilla (Center for Economic Studies and ifo Institute (CESifo), 2014)
We develop a theoretical analysis of two widely used regulations of genetic tests, disclosure duty and consent law, and we run several experiments in order to shed light on both the take-up rate of genetic testing and on the comparison of policyholders' welfare under the two regulations. Disclosure Duty forces individuals to reveal their test results to their insurers, exposing them to the risk of having to pay a large premium in case they are discovered to have a high probability of developing a disease (a discrimination risk). Differently, Consent Law allows them to hide this detrimental information, creating asymmetric information and adverse selection. We obtain that the take-up rate of the genetic test is low under Disclosure Duty, larger and increasing with adverse selection under Consent Law. Also, the fraction of individuals who are prefer Disclosure Duty to Consent Law increases with the amount of adverse selection under the latter. These results are obtained for exogenous values of adverse selection under Consent Law, and the repeated interactions experiment devised has not resulted in convergence towards an equilibrium level of adverse selection.
Keywords: D82; I18; C91; 330; disclosure duty; consent law; discrimination risk; informational value of test; personalized medicine; experiment